Hypertension-Related Knowledge and Medication Adherence among Hypertensive Patients Residing in Urban Slums of Ahmedabad City: A Community-Based Cross-Sectional Study - Vaishali Patel; Nirali Patel; Chintul Shah (International Journal of Health Sciences and Research, 2026)
Background: Inadequate knowledge of hypertension may hinder effective self-management and long-term medication adherence, particularly in underserved communities. Objectives: To assess the level of knowledge regarding hypertension, to study its association with medication adherence, and to identify the factors affecting the knowledge of hypertension among diagnosed patients residing in urban slums of Ahmedabad city. Methods: A community-based cross-sectional study was conducted from September to December 2019 among 562 adults with diagnosed hypertension residing in urban slums of Ahmedabad city. Participants were selected using zone-wise probability-proportionate-to-population sampling followed by household-level sampling. Data were collected using a pre-tested semi-structured questionnaire. Hypertension knowledge was assessed using a 15-item scale and categorized as poor (≤8), average (9–12), or good (13–15). Medication adherence was assessed using the 8-item Morisky Medication Adherence Scale (MMAS-8). Data were analysed using Microsoft Excel 2016 and the chi-square test, with p